Evidence-based guidelines in the evaluation of work disability: an international survey and a comparison of quality of development - Donceel Peter; Rijkenberg Arie M; Bruinvels David J; de Boer Wout EL; Anema Johannes R (BMC, 2009)
Abstract Background In social insurance, the evaluation of work disability is becoming stricter as priority is given to the resumption of work, which calls for a guarantee of quality for these evaluations. Evidence-based guidelines have become a major instrument in the quality control of health care, and the quality of these guidelines' development can be assessed using the AGREE instrument. In social insurance medicine, such guidelines are relatively new. We were interested to know what guidelines have been developed to support the medical evaluation of work disability and the quality of these guidelines. Methods Five European countries that were reported to use guidelines were approached, using a recent inventory of evaluations of work disability in Europe. We focused on guidelines that are disease-oriented and formally prescribed in social insurance medicine. Using the AGREE instrument, these guidelines were appraised by two researchers. We asked two experts involved in guideline development to indicate if they agreed with our results and to provide explanations for insufficient scores. Results We found six German and sixteen Dutch sets of disease-oriented guidelines in official use. The AGREE instrument was applicable, requiring minor adaptations. The appraisers reached consensus on all items. Each guideline scored well on 'scope and purpose' and 'clarity and presentation'. The guidelines scored moderately on 'stakeholder involvement' in the Netherlands, but insufficiently in Germany, due mainly to the limited involvement of patients' representatives in this country. All guidelines had low scores on 'rigour of development', which was due partly to a lack of documentation and of existing evidence. 'Editorial independence' and 'applicability' had low scores in both countries as a result of how the production was organised. Conclusion Disease-oriented guidelines in social insurance medicine for the evaluation of work disability are a recent phenomenon, so far restricted to Germany and the Netherlands. The AGREE instrument is suitably applicable to assess the quality of guideline development in social insurance medicine, but some of the scoring rules need to be adapted to the context of social insurance. Existing guidelines do not meet the AGREE criteria to a sufficient level. The way patients' representatives can be involved needs further discussion. The guidelines would profit from more specific recommendations and, for providing evidence, more research is needed on the functional capacity of people with disabilities.